The ideological components of populism and conspiracy theories - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2021)
There has been a lot of research on populism and conspiracy theories in the last century, and there is one thing in common in all researches․ In almost all studies, populism and conspiracy theories are viewed as threatening the democracy, the establishment of a rational, constructive social-political dialogue. However, the ideological and content generalities of populism and conspiracy theories have not been sufficiently studied in the professional literature. In this study the general ideological components of populism and conspiracy theories have been summarized and some of the descriptive elements of populist conspiracy theories have been identified. These components are the machiavellian understanding of politics, the stratification of society on the basis of moral opposition ("good people" - "evil elite"), the demonization of elites, the mythological modeling of social-political processes.
Keywords: “thin” ideology; populism; theory about conspiracy; conspiracy theory; Machiavellianism; ideological component; anti-elitism